Efeito da aplicação da kinesio taping na disfunção temporomandibular miogênica localizada: análise algométrica, eletromiográfica e termográfica - Dutra, Cynthia Maria Rocha (2017)
Introduction: myogenic temporomandibular disorders (TMD) is a condition that should have multidisciplinary assistance. In this regard, the Kinesio Taping technique (KT) is a therapeutic alternative. Objectives: to evaluate systematically the Physical Therapy and Speech Therapy interventions used in the treatment of TMD studies (Article 1); to evaluate the effectiveness of KT therapy in the treatment of pain associated with musculoskeletal disorders (Article 2); to investigate the acute effects of applying KT in patients with myogenic TMD disorders (Article 3). Methods: for Articles 1 and 2, the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines were followed and registered in the Prospective International Register of Systematic Reviews (PROSPERO). A search using specific key words for Article 1 ("temporomandibular dysfunction,” “temporomandibular joint,” “physiotherapy, speech therapy,” and “pain"), and for Article 2 (“kinesiotape,” “kinesio taping,” “pain,”“functional recovery,” “rehabilitation,” and “algometry") was completed. The study in Article 3, which involved a double-blind randomized controlled clinical trial, was performed at the Clinical School of Physiotherapy, University of Tuiuti of Parana. The study and assessed pain, electromyography, and thermography results at baseline and after three days of the intervention. An experimental group (KTG) received KT, and a control group (CG) received adhesive tape (placebo). Results: article 1 – of 501 articles found, four were included in the review, which pointed out that a multidisciplinary approach for the management of myogenic TMDs is appropriate. Article 2 – which returned 388 articles and included 15 in the review, most were found to be published in Europe, indicating that there was no consensus on the use of KT, and suggesting that a multidisciplinary interaction seems to be essential for the treatment of myogenic TMD. Article 3 – 70 participants, selected based RDC/TMD, randomly assigned to KTG (27 women, 8 men, middle age 29.71 ± 8.66) and GC (29 women, 6 men, middle age 32.37 ± 8.58). There was no difference in the EMG between KTG and CG in the masseter (p = 0.1494) and temporal (p = 0.699395) muscle. There was a decrease in the values of thermography in the KTG (33.43 ± 0.12 for 32.51 ± 0.21), and maintenance in CG (33.43 ± 0.13 for 33.42 ± 0.2). No significant difference was observed in algometry (0.05673 KTG), with a tendency for improvement, being significant for the CG (p = 0.02245). The data of lower degree of pain, in the KTG, compared to before the experiment, confirm the findings of the EMG results. Conclusion: it was surmised that KT results in an improvement in myogenic TMD symptomatology after a single application. However, further research is needed to determine the medium- and long-term effects of the technique. As a non-invasive and painless method, as an option for treatment, it is an indicated technique, having to take into account the methodology and the time of permanence with the KT that may influence the functional recovery and the analgesia. However, based on crossing data collected in the articles and in the interventions, and taking into account the number of inconsistent and conflicting reports on their effects, we see the need for an appropriate and necessary multidisciplinary approach for the management of myogenic TMD, in particular by using complementary therapy that could potentiate the effects of the treatment.